Hegel intérprete de Aristóteles : a questão teleológica na filosofia da história hegeliana - França, Lincoln Menezes de (Universidade Federal de São Carlos, 2017)
For G.W.F. Hegel (1770-1831), the historical deployments demonstrate as a whole a progression in the recognition of the Self of the Spirit and the knowledge of freedom, which enables the philosophy of history to verify the effectiveness of reason in the world and the progressive achievement of the absolute ultimate End purpose. As Hegel considers that the conception of purpose is the main determination that arrives at us from the Aristotelian philosophy, the central objective of this thesis is to understand the role of the Aristotelian philosophy of the history of Hegel. The singularity of the Hegelian teleological conception is characterized by resorting to Aristotelian philosophy as a necessary moment for Hegel's reaction to Kantian and post-Kantian idealism, providing greater clarity about Hegel's understanding of the teleological question in history and its relation to its conception of the history of philosophy according to its own conceptual heritage. The analytical starting point of this thesis is the Phenomenology of the Spirit, a work in which Hegel develops the introduction to his philosophical system and also presents a peculiar teleological perspective, which is systematically exposed later in the texts of the Science of Logic and the Encyclopedia of Philosophical Sciences. These works of systematic character has a central importance for the understanding of the teleological question in the Lectures on the Philosophy of History, since they are deployments of their own philosophical system. In the Lectures on the History of Philosophy there is a more detailed exposition of Aristotelian philosophy and the teleological question. However, the philosophical problems faced by Hegel are specific to his time, which implies conceptual peculiarities concerning teleology in the Hegelian system and, consequently, in the Philosophy of History. In addition, Hegel has a very specific conception of the interpretation of the history of philosophy, linked to the systematic notion of the development of the Spirit. In this sense, by accepting a conceptual heritage in relation to Aristotelian teleology, Hegel searches one more internal coherence for his own systematic conception of the history of philosophy, in other words, one conception where there is a progression of the Spirit from which Aristotle and the other philosophers were part of it, rather than a philosophical fidelity or a strict conceptual affiliation to Aristotle.
Keywords: Hegel; Aristóteles; Teleologia; História; Aristotle; Teleology; History; CIENCIAS HUMANAS::FILOSOFIA